DAM: Hierarchical Adaptive Feature Selection Using Convolution Encoder Decoder Network for Strawberry Segmentation - Ilyas, Talha; Umraiz, Muhammad; Khan, Abbas; Kim, Hyongsuk (Frontiers in Plant Science, 2021)
Autonomous harvesters can be used for timely cultivation of high-value crops such as strawberries, where the robots have the capability to identify ripe and unripe crops. However, real-time segmentation of strawberries in unbridled farming environment is a challenging task due to fruit occlusion by multiple trusses, stems and leaves. In this work we propose a possible solution by constructing a dynamic feature selection mechanism for convolutional neural networks (CNN). The proposed building block namely dense attention module (DAM), controls the flow of information between convolutional encoder and decoder. DAM enables hierarchical adaptive feature fusion by exploiting both inter-channel and intra-channel relations and can be easily integrated into any existing CNN to obtain category specific feature maps. We validate our attention module through extensive ablation experiments. In addition, a dataset is collected from different strawberry farms and divided into four classes corresponding to different maturity levels of fruits and one is devoted to background. Quantitative analysis of the proposed method showed 4.1% and 2.32% increase in mean Intersection over Union, over existing state of the art semantic segmentation models and other attention modules respectively, while simultaneously retaining a processing speed of 53 frames per second.